THE INFLUENCE OF THE CREATIVE KAMPONG’S TOURIST ACTIVITIES ON THE CHANGE IN LAY-OUT FOR ACTIVITIES AND THE CHANGE IN SPATIAL ARRANGEMENT OF THE DAGO POJOK KAMPONG IN BANDUNG - Maria Kencana Hanggana Raras ; Giosia P. Widjaja (Riset Arsitektur (RISA), 2018)
Abstract - “Bandung the Champ” is a program organized by Bandung’s Municipal Government to develop the local economy and increase the quality of urban life. One of these programs is called the Kampong Champ, which puts forward the concept of the Creative Kampong. The purpose of this program is to develop the economy of the local community by way of exploring the potential of the citizens, and to create a kampong fit for tourism. The Creative Kampong at Dago Pojok has been built and expanded from 2010 up to the present. The phenomenon that has taken place consists of the change made in the spatial lay-out to accommodate tourist activities based in these quarters that are of a temporary kind. This research project aims to identify the change mentioned above as a consequence of the marked shift from daily activities in the neighborhood to tourism-related ones and to reveal the influence of the change in spatial arrangement made in this kampong on the spatial lay-out of the Dago Pojok area. The methods employed for this research consist of the qualitative method and the descriptive method along with field observation using the technique of observing place-centered mapping. The study of the discussion starts off with identifying the arrangement of physical space that has undergone change due to a change in activity, followed by an analysis of the influence of the architectural elements on the change made in the lay-out of physical space and the approach to the morphological aspects of the city to identify the impact of these changes on the planning of this urban area. The results of the study indicate that the changes made in the arrangement of the activity space and the circulation have been caused by the change in daily activities into tourism-related ones coming from the Creative Kampong so that the latter’s spatial lay-out cannot accommodate these activities properly. As a consequence, the space needs to be rearranged with the element of semi-fixed features due to the density of the relatively tall buildings in this urban kampong. The changes in spatial arrangement made in the various areas under observation have exerted an influence on the urban kampong’s spatial lay-out, amounting to a structural change in the lay-out and orientation as well as the formation of hierarchy and datum in the area of Dago Pojok. Keywords : Tourism, Creative Kampong, change in lay-out, change in spatial arrangement